2017
DOI: 10.1038/s41598-017-03781-y
|View full text |Cite
|
Sign up to set email alerts
|

Seabirds supply nitrogen to reef-building corals on remote Pacific islets

Abstract: Seabirds concentrate nutrients from large marine areas on their nesting islands playing an important ecological role in nutrient transfer between marine and terrestrial ecosystems. Here we investigate the role of guano on corals reefs across scales by analyzing the stable nitrogen isotopic (δ15N) values of the scleractinian coral Pocillopora damicornis on fringing reefs around two Pacific remote islets with large seabird colonies. Marine stations closest to the seabird colonies had higher nitrate + nitrite con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 77 publications
5
82
0
Order By: Relevance
“…Corals assimilate nutrients from seabirds nesting on adjacent islands (Lorrain et al, 2017), and the ratio of nitrogen to phosphorous in seawater adjacent to seabird colonies is within the range considered optimal for increasing coral growth, photosynthetic efficiency and resistance to heat stress (N:P ratio of 13-32 in seawater compared to optimal ratio of 11-29; Allgeier et al, 2014;Savage, 2019;Wiedenmann et al, 2013). Corals assimilate nutrients from seabirds nesting on adjacent islands (Lorrain et al, 2017), and the ratio of nitrogen to phosphorous in seawater adjacent to seabird colonies is within the range considered optimal for increasing coral growth, photosynthetic efficiency and resistance to heat stress (N:P ratio of 13-32 in seawater compared to optimal ratio of 11-29; Allgeier et al, 2014;Savage, 2019;Wiedenmann et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corals assimilate nutrients from seabirds nesting on adjacent islands (Lorrain et al, 2017), and the ratio of nitrogen to phosphorous in seawater adjacent to seabird colonies is within the range considered optimal for increasing coral growth, photosynthetic efficiency and resistance to heat stress (N:P ratio of 13-32 in seawater compared to optimal ratio of 11-29; Allgeier et al, 2014;Savage, 2019;Wiedenmann et al, 2013). Corals assimilate nutrients from seabirds nesting on adjacent islands (Lorrain et al, 2017), and the ratio of nitrogen to phosphorous in seawater adjacent to seabird colonies is within the range considered optimal for increasing coral growth, photosynthetic efficiency and resistance to heat stress (N:P ratio of 13-32 in seawater compared to optimal ratio of 11-29; Allgeier et al, 2014;Savage, 2019;Wiedenmann et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our prediction, hard corals declined regardless of whether they were adjacent to islands with seabirds or islands with invasive rats. Corals assimilate nutrients from seabirds nesting on adjacent islands (Lorrain et al, 2017), and the ratio of nitrogen to phosphorous in seawater adjacent to seabird colonies is within the range considered optimal for increasing coral growth, photosynthetic efficiency and resistance to heat stress (N:P ratio of 13-32 in seawater compared to optimal ratio of 11-29; Allgeier et al, 2014;Savage, 2019;Wiedenmann et al, 2013). Therefore, we expected the large inputs of nitrogen and phosphorous from seabird guano to enhance resistance of corals to bleaching (D'Angelo & Wiedenmann, 2014;Graham et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient levels vary in nature with the water quality, the upwellings, the stratification of the water column, the seasonality or the presence of fish and bird colonies on the surrounding islands [ 57 , 58 , 59 ]. Reefs are generally oligotrophic, with ca.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that global seabirds inputs of N and P are respectively of 591 Gg y -1 and 99 Gg y -1 , with the Antarctic and Southern Ocean coasts receiving the highest amounts, roughly 80% whereas these areas 26% of the global seabird population (Otero et al, 2018). Moreover, various authors (Ellis et al, 2006;Lorrain et al, 2017;Otero et al, 2015;Sutton et al, 2013) suggested that seabird colonies represent a positive geochemical anomaly (i.e., above background values) regarding the concentrations of N and P present in soils, sediments, and water, hence the term ornithoeutrophication (Otero et al, 2018). It is, therefore, reasonable to assume that seabird colonies enrich their ecosystems as a whole, in a mass balance perspective.…”
Section: A Mass Balance Perspectivementioning
confidence: 99%